Reversible methane storage in porous hydrogel supported clathrates - Ding, Ailin; Yang, L.; Fan, S.; Lou, Xia (Pergamon, 2013)
Methane gas hydrates are a promising alternative for storage and transport of natural gas. In this paper, porous poly(2-hydroxyethyl methacrylate) (PHEMA) and poly(2-hydroxyethyl methacrylate-co-methacrylic acid) (PHEMA-co-MAA) hydrogel microspheres were synthesised and examined for their application as a reusable scaffold for methane storage in their hydrated form. The hydration kinetics, methane storage capacity of the hydrogel microspheres, and a mixed colloidal system made of hydrogel particles and dry-water droplets were investigated in a 300cm3 steel vessel at 273.2K and varying pressures. Hydration of methane in the mixed colloidal system is high in capacity and exceedingly reversible. Higher pressure and smaller size of hydrogel microspheres result in improved capacity and kinetics, however reduce the recyclability of hydration. The porous hydrogel particles alone are too soft for reuse and need to be improved for practical application. Porous hydrogel microspheres were synthesised and mixed with dry-water, forming a colloidal system. Formation of methane gas hydrates in the colloidal system was fast, and high in hydration capacity. The system is reusable for methane storage.